Measurements of aerial biomass of Cenchrus ciliaris L. under the arid bioclimate of Tunisia - Abdelkader I.; Ferchichi A.; Chaieb M. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
The main objective of this work was to assess the above-ground biomass of Cenchrus ciliaris under the arid climate of Tunisia. Measurements of volume parameters (height, crown diameters and biovolume) and biomass production were made during 2003-2006. Different regression models between these parameters were tested. Results showed high significant relationships between total biomass production and mean crown diameter (R2 varied from 0.62 to 0.71). Annual production had the lowest correlation with mean diameter (R2 varied from 0.43 to 0.51). Linear regression between the total biomass production of C. ciliaris and both height and crown diameters had a high significant relationship (R2=0.75). Whereas, linear regression between annual biomass production and these volume parameters generated a model equation with lower coefficient of determination (R2=0.51).
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)